(untitled) (REMUNOM, 2025)
Objective: To analyze the relationship between the work environment and the use of psychotropic drugs by nurses. Methods: A cross-sectional analytical study was conducted with 87 nurses from the Municipal Health Department of a city in the metropolitan region of Goiânia, Goiás. The data, collected remotely, covered sociodemographic and professional characteristics, dichotomization of the work environment as favorable or unfavorable to professional practice, mental health conditions, and use of psychotropic drugs. The data were analyzed using tests, descriptive analysis, reliability, and consistency. The analyses were considered statistically significant. Results: Among the participants, 32.2% used psychotropic drugs, 56.3% considered themselves anxious, 50% reported a diagnosis of anxiety, 70.5% considered work an important factor for this use, and 51.7% assessed the work environment as unfavorable to professional practice. Conclusion: The results suggest that nurses are potentially susceptible to the use of psychotropic drugs due to physical and mental exhaustion. The inappropriate and abusive use of these drugs can cause harm to nurses, patients, and health services. The nurses in the sample indicated that their work environment was unfavorable to professional practice and stated that work contributes to mental illness in the category, highlighting it as a relevant factor in the use of psychotropic drugs. This study offers important insights for reflection on the work environment as a risk factor for mental illness and reinforces the need to develop strategies for promoting, preventing, and protecting nurses’ mental health.